Bibliometric Assessment and Research Trends : Five Decades of Brand Image - Siti Aisyah, Ya'kob; Rohaizat, Baharun; Siti Ngayesah, Ab Hamid; Masilah, Mohamad (UKM Press, 2024)
Brand image distinguishes a company, product, or service from others, making it an asset worth investing in. Recognizing the key themes related to brand image is essential for fostering collaboration and ensuring that research progresses toward desired goals. Therefore, this bibliometric study’s objective was to uncover global research trends on the topic of brand image based on publishing output, co-authorship, country, and co-occurrence. We used the Scopus indexing database to identify 2,605 relevant papers published from January 1971 to November 2021. Utilizing the VOSViewer application, bibliometric procedures were subsequently employed to analyze the global performance, development, and impact of brand image research. Our results revealed that: the USA has the most brand image-related publications; the majority of brand image articles have been published in Scopus Quartile 1 journals; and the most recent author keywords are social media, perceived value, and purchase intention. By tracking the origins and evolution of brand image research over time, this article’s originality serves as a reference point for expanding the literature on brand image and providing directions for future study.